TNFα Induces Choroid Plexus Epithelial Cell Barrier Alterations by Apoptotic and Nonapoptotic Mechanisms. (30th March 2010) - Schwerk, Christian; Rybarczyk, Kasia; Essmann, Frank; Seibt, Annette; Mölleken, Marie-Louise; Zeni, Patrick; Schroten, Horst; Tenenbaum, Tobias
Abstract : The choroid plexus epithelium constitutes the structural basis of the blood-cerebrospinal fluid barrier. Since the cytokine TNFα is markedly increased during inflammatory diseases in the blood and the central nervous system, we investigated by which mechanisms TNFα induces barrier alteration in porcine choroid plexus epithelial cells. We found a dose-dependent decrease of transepithelial electrical resistance, increase of paracellular inulin-flux, and induction of histone-associated DNA fragmentation and caspase-3 activation after TNFα stimulation. This response was strongly aggravated by the addition of cycloheximide and could partially be inhibited by the NF-κ B inhibitor CAPE, but most effectively by the pan-caspase-inhibitor zVAD-fmk and not by the JNK inhibitor SP600125. Partial loss of cell viability could also be attenuated by CAPE. Immunostaining showed cell condensation and nuclear binding of high-mobility group box 1 protein as a sign of apoptosis after TNFα stimulation. Taken together our findings indicate that TNFα compromises PCPEC barrier function by caspase and NF-κ B dependent mechanisms.